Analisis Pemanfaatan Pojok Baca Dalam Meningkatkan Minat Literasi Siswa Kelas IV di MI Ar-Raudlah - Raysa Eka Delvira; Mutia Salza Bilannur; Levina Galuh; Rizky Tidarwati Pratiwi; Abdi Dwi Andika Putra; Ahmad sudi pratikno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the condition of literacy and analyze the use of reading corners in increasing the literacy interest of grade IV students in MI-Ar-Raudlah. This research uses a qualitative descriptive approach with a type of field research. Data collection techniques are carried out through observation, interviews, questionnaires, documentation, field notes, and student literacy pre-tests. The results of the study show that the lack of reading corner facilities and school libraries causes literacy activities to not run optimally. Student reading activities are still limited to the use of textbooks during the learning process. In addition, students' reading interest is relatively low to moderate, and the ability to understand reading still needs to be improved, especially in finding the main idea and understanding the content of the reading text. However, the existence of a reading corner is considered to have the potential as a means of supporting in improving literacy culture and the habit of reading in elementary schools. Therefore, more optimal facility support and literacy management are needed to create a learning environment that supports the development of student literacy. Keywords: Reading Corner, Literacy Interest, Elementary School.